Exploring Diverse Thinking Level Students Challenge and Strategy in Solving English Language HOT Question - Satyaputri, Talitha Rizky; Soraya, Irma (New Language Dimensions, 2020)
The role of higher order thinking skill in the instructional process is undeniably essential especially in this millennial era that demands more critical thinking. However, the unpleasant fact showed that Indonesian students are still unfamiliar and having difficulty to solve HOTS question. Although HOTS has been implemented in Indonesia since 2013. One English language activity that involves HOTS the most is writing. That fact leads this present study to examine; 1)  students challenge in solving HOT question for English writing, and 2) students strategies in solving HOT question. On top of that, present study also examined the challenge and strategy based on diverse students thinking level. Researcher used descriptive qualitative method and for obtaining the data, researcher conducted a HOTS testing to determine students thinking level then conducted interview with the students representative from each thinking level to fulfil both of the research questions. The result highlighted that the same level of thinking students indeed had some different challenges and vice versa. Additionally, cognitive challenge becomes the major challenge comparing to the linguistic ones from both of HOT and LOT students perspective. Then, the strategies that was implemented by students are ; 1) estimating the time, 2) re-reading the HOT question, 3) translating the question, 4) Paraphrasing the question, 5) pointing important keywords, 6) getting background knowledge from semantic and episodic memory, 7) asking peers for help, 8) scratching raw idea, 9) rereading the whole answer and self-reflecting. Overall LOT applied more strategies than HOT students.